2007
DOI: 10.1016/j.matbio.2006.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin promotes pathologic mineralization in articular cartilage

Abstract: Calcium pyrophosphate dihydrate (CPPD) crystals are commonly found in osteoarthritic joint tissues, where they predict severe disease. Unlike other types of calcium phosphate crystals, CPPD crystals form almost exclusively in the pericellular matrix of damaged articular cartilage, suggesting a key role for the extracellular matrix milieu in their development. Osteopontin is a matricellular protein found in increased quantities in the pericellular matrix of osteoarthritic cartilage. Osteopontin modulates the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…41 Furthermore, TG2 transamidation of OPN promotes OPN dimerization and crosslinking to collagen 42 and alters the capacity of OPN to regulate calcium-containing crystal deposition in the extracellular matrix. 43 The physiological significance of the relationship between TG2 and OPN in calcified arteries was recently highlighted by the discovery that most of the OPN extracted from MGP Ϫ/Ϫ mouse aortas is polymerized in association with TG2 expression and isopeptide bond formation. 44 Adhesion to the basement membrane protein laminin (or to collagen I fibrils) normally promotes retention of contractile SMC differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…41 Furthermore, TG2 transamidation of OPN promotes OPN dimerization and crosslinking to collagen 42 and alters the capacity of OPN to regulate calcium-containing crystal deposition in the extracellular matrix. 43 The physiological significance of the relationship between TG2 and OPN in calcified arteries was recently highlighted by the discovery that most of the OPN extracted from MGP Ϫ/Ϫ mouse aortas is polymerized in association with TG2 expression and isopeptide bond formation. 44 Adhesion to the basement membrane protein laminin (or to collagen I fibrils) normally promotes retention of contractile SMC differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the association of OPN with cartilage degradation, it has been shown that the expression of OPN protein and mRNA increases along with the severity of OA (22). In addition, OPN has been known to act as a regulator of pathologic mineralization in articular cartilage (39). However, other functional roles of OPN in OA pathogenesis have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, transglutaminase (TG)2 stimulates covalent S100A11 homodimerization by catalyzing formation of N-(␥-glutamyl)lysyl isopeptide bonds (29,30). Moreover, cultured articular chondrocytes express TG2 (31), and TG catalytic activity and TG-catalyzed isopeptide bond formation are substantially increased in human knee OA cartilage chondrocytes (32,33). Furthermore, TG2 is the principal catalytically active TG isoenzyme in OA cartilage extracellular matrix in situ (34).…”
mentioning
confidence: 99%